On Super (a,d)-edge antimagic total labeling of branched-prism graph - Khairannisa Al Azizu; Lyra Yulianti; Narwen Narwen; Syafrizal Sy (Indonesian Journal of Combinatorics, 2021)
Let H be a branched-prism graph, denoted by H = (Cm x P2) ⊙ Ǩn for odd m, m ≥ 3 and n ≥ 1. This paper considers about the existence of the super (a,d)-edge antimagic total labeling of H, for some positive integer a and some non-negative integer d.